Antimicrobial Resistance and Virulence-Associated Traits of Campylobacter jejuni Isolated From Poultry Food Chain and Humans With Diarrhea - Wieczorek, Kinga; Wołkowicz, Tomasz; Osek, Jacek (Frontiers in Microbiology, 2018)
The objective of this study was to test the prevalence of virulence-associated markers and antimicrobial resistance in 624 C. jejuni isolated from poultry food chain, i.e. chicken feces (n = 160), poultry carcasses (n = 157), poultry meat (n = 152) and from humans (n = 155). All human strains were positive for 9 out of 13 putative virulence genes responsible for expression of pathogenic factors involved in different stages of the infection. The presence of all markers was also high in strains from chicken feces, carcasses and meat although not all of them were identified in 100% of the isolates. On the other hand, the virB11, wlaN and iam putative pathogenic genes were detected in only 1.9%, 15.2% and 20.5% of strains, respectively. C. jejuni isolates, irrespective of the origin, were highly resistant to ciprofloxacin (92.5% isolates), followed by nalidixic acid (88.9%) and tetracycline (68.4%). In case of ciprofloxacin, significantly more isolates from poultry feces, carcasses and meat were resistant than those obtained from humans and the same relationship was observed for tetracycline where the isolates from chicken feces were more often resistant than C. jejuni of carcasses and meat origin. A low number of strains was resistant to streptomycin (18.4% isolates) and only 5 strains (0.8%) displayed resistance to erythromycin. A relationship between resistance to fluoroquinolones and presence of selected pathogenic markers was observed, e.g. from 83.3% strains with the virB11 to 93.4% with the docA genes were resistant to ciprofloxacin. The isolates that did not possess any of the pathogenic traits were also mainly resistant to this antimicrobial, although the number of such strains was usually low, except virB11 (612 isolates), wlaN (529 strains), and iam (496 isolates). Furthermore, resistance to tetracycline was somehow associated with the presence of the virulence associated genes wlaN and virB11 (56.8% and 75.0% isolates, respectively). The present study shows a high antimicrobial resistance to quinolones and tetracycline of C. jejuni isolated along poultry food chain and from patients with diarrhea, which was closely correlated with the presence of several virulence genes playing a role in the pathogenesis of Campylobacter infection.